A Viking Age weight from Cleat, Westray, Orkney - Maleszka, Monika (Proceedings of the Society of Antiquaries of Scotland, 2004)
A Viking-period barrel-shaped weight, found at Cleat, on Westray, is discussed in the context of other weights and contemporary Islamic and Scandinavian/Islamic weight systems.